New Institutional Economics: A Critique of Fundamentals & Broad Strokes Towards an Alternative Theoretical Framework for the (Asian Journal of Social Science Studies, 2018)
This article explicitly deals with and scrutinises what can be perceived to be the core analytical issues and methodological concepts of new institutional economics. New institutionalism seeks to explain not just the origins and evolution of institutions of capitalism, but more generally the scope of the theory is supposed to be universally applicable. Granted this, new institutionalists often interpret the historical emergence and evolution of institutions in abstract logical terms. This is because of the static, timeless, ahistorical and asocial nature of marginalism and neoclassical equilibrium analysis used by new institutionalists. Hence, an attempt is made to propose certain methodological and theoretical premises that can pave the way for the construction of an alternative, qualified theory of institutional arrangements. In this vein, the issues of social structure, social relations, power and conflict come to central stage.